Enhancing Campus Communication: Advanced ML Techniques for College Chatbots - Annapoorna, CM; Ushasree, R (INTI International University, 2024)
This research explores the development and deployment of a college chatbot using advanced machine learning techniques to enhance communication and support within the campus community. The chatbot is designed to efficiently handle a variety of student inquiries by leveraging natural language processing and deep learning models. Through a detailed methodology, evaluation of metrics, and real-world testing, this study demonstrates how the chatbot enhances student engagement and administrative efficiency. Challenges encountered during development included managing ambiguous queries and ensuring data accuracy and relevance. Future work aims to expand the chatbot's capabilities with personalized interactions, voice-based queries, and multilingual support to better serve a diverse student body and further improve functionality. This research paper provides an analysis of designing, applying, and utilizing a college chatbot’s powered by advanced ML techniques. The functions demonstrate its prospective to rationalize campus communication, offering a scalable, efficient, and user-friendly solution to meet the changing needs of modern educational institutions.